Pengaruh Teologi Terhadap Perbuatan Dan Sikap Hidup Manusia - Basori, Basori (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2002)
In Islamic studies, theology is put in a central position as it not only clarifies the basic Islam concepts, but also has a significant role in determining Moslem attitude. The great advanced of Moslem civilization among others, was supported by the strong influence of rational theology initiated by Mutazillah. For this reason, Nasution believes that civilization of Moslem world is determined by the theology thought they believe. If modern people believe in a rational way of life, then, traditional theology becomes a significant pre- requisite.